1997
DOI: 10.23986/afsci.72792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of variety, soil type and nitrogen fertilizer supply on the nutritive value of barley for growing pigs

Abstract: The effects of variety, soil type and nitrogen (N)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
3
6
0
Order By: Relevance
“…No significant differences in CA considering management system, years and mineral N fertilising could be confirmed (Tables 3 and 4). This is similar with results of Peers and Taylor (1977) and Valaja et al (1997), but not with findings of Jørgensen et al (1999) who found significant decrease in the CA content with increased mineral N rates.…”
Section: Ash Contentsupporting
confidence: 91%
See 4 more Smart Citations
“…No significant differences in CA considering management system, years and mineral N fertilising could be confirmed (Tables 3 and 4). This is similar with results of Peers and Taylor (1977) and Valaja et al (1997), but not with findings of Jørgensen et al (1999) who found significant decrease in the CA content with increased mineral N rates.…”
Section: Ash Contentsupporting
confidence: 91%
“…Even more, each mineral N rate significantly increased CP content (Table 5). The same results were obtained in the experiment of Èeh Brenik and Tajnek (2000), Peers and Taylor (1977), and by many others authors, in the experiment of Valaja et al (1997) higher mineral N rate caused higher CP content. Although the protein content was increasing with increased mineral N rate from 9.214.2% (Table 5) (by 35%) ME content and NEL content did not differ considering mineral N rate (Table 3).…”
Section: Crude Protein Contentsupporting
confidence: 87%
See 3 more Smart Citations